Analysis of Chromatin Regulators Reveals Specific Features of Rice DNA Methylation Pathways. Issue 3 (12th May 2016) - Tan, Feng; Zhou, Chao; Zhou, Qiangwei; Zhou, Shaoli; Yang, Wenjing; Zhao, Yu; Li, Guoliang; Zhou, Dao-Xiu
Abstract : The methyl-transferases OsDDM1 and OsDRM2 display functional specificities that define distinct DNA methylation pathways in the bulk of DNA methylation of the rice genome. Abstract: Plant DNA methylation that occurs at CG, CHG, and CHH sites (H = A, C, or T) is a hallmark of the repression of repetitive sequences and transposable elements (TE s). The rice ( Oryza sativa ) genome contains about 40% repetitive sequence and TE s and displays specific patterns of genome-wide DNA methylation. The mechanism responsible for the specific methylation patterns is unclear. Here, we analyzed the function of OsDDM1 (Deficient in DNA Methylation 1) and OsDRM2 (Deficient in DNA Methylation 1) in genome-wide DNA methylation, TE repression, small RNA accumulation, and gene expression. We show that OsDDM1 is essential for high levels of methylation at CHG and, to a lesser extent, CG sites in heterochromatic regions and also is required for CHH methylation that mainly locates in the genic regions of the genome. In addition to a large member of TE s, loss of OsDDM1 leads to hypomethylation and up-regulation of many protein-coding genes, producing very severe growth phenotypes at the initial generation. Importantly, we show that OsDRM2 mutation results in a nearly complete loss of CHH methylation and derepression of mainly small TE -associated genes and that OsDDM1 is involved in facilitating OsDRM2-mediated CHH methylation. Thus, the function of OsDDM1 and OsDRM2 defines distinct DNA methylation pathways in the bulk of DNA methylation of the genome, which is possibly related to the dispersed heterochromatin across chromosomes in rice and suggests that DNA methylation mechanisms may vary among different plant species.